IMPLEMENTATION OF REGIONAL GOVERMENT INFORMATION SYSTEM (SIPD) IN MUNA BARAT REGENCY: AN E-GOVERNMENT ANALYSIS USING NVIVO - Sudirman, Faturachman Alputra; Saidin, Saidin; Maswa, Sitti; Susilawaty, Fera Tri (Laboratorium Ilmu Komunikasi Fisip UHO, 2025)
This study aims to examine the implementation of the Regional Development Information System (SIPD) at the Regional Development Planning Agency (Bappeda) of Muna Barat Regency, Southeast Sulawesi, and the factors influencing its implementation. The method used is a descriptive qualitative approach with data collection through interviews, official documents, archives, and data analysis using Nvivo software. The results show that the implementation of SIPD faces various challenges, including server errors, inadequate network access, and the need to improve the quality of human resources. Analysis based on the three success elements from Harvard JFK School of Government (Support, Capacity, and Value) indicates that regulatory support, capacity building of human resources, and leadership support are key factors in the successful implementation of SIPD. Leadership support and ongoing training are crucial for overcoming obstacles and enhancing the system's effectiveness and efficiency. This study provides significant contributions by offering a comprehensive view of the factors influencing the implementation of SIPD and providing recommendations to improve public service quality and transparency in regional government.